Comparing Web of Science, Scopus and Google Scholar from an Environmental Sciences perspective - Leslie S. Adriaanse; Chris Rensleigh (South African Journal of Libraries and Information Science, 2011)
This paper presents a macro- and micro-level comparison of the citation resources Web of Science (WOS), Scopus and Google Scholar (GS) for the environmental sciences scholarly journals in South Africa during 2004-2008. The macro-level measuring instruments consisted of 26 evaluation criteria with the following broad categories: content, access, services, interface, searching, search results, cost, citation and analytical tools, and linking abilities. The micro-level measuring instrument’s evaluation criteria represented the data fields of the journal records to establish comprehensivity. The macro-level evaluation results indicated that Scopus surpassed both WOS and GS whereas the micro-level evaluation results indicated that WOS surpassed both Scopus and GS. Based on the macro- and micro-level evaluation results the study was able to establish that GS is not yet a substitute but rather a supplementary citation resource for the fee-based WOS and/or Scopus for the South African international accredited scholarly environmental sciences journals during the period 2004-2008.